Answer:
Step-by-step explanation:
Answer:
.125
Step-by-step explanation:
Answer:
If q, then p
Step-by-step explanation:
The given conditional statement is "If p, then q"
We want to find the converse of this conditional statement.
The converse is formed by switching the hypothesis (p) and the conclusion (q).
Therefore the converse of the given conditional is "If q, then p"
Answer:
a. 8 cm
Step-by-step explanation:
Given:
EH = 6 cm
FG = 4.00 cm
Based on the mid-segment theorem of a trapezoid, we have:
EH = ½(FG + DI)
Plug in the values
6 = ½(4 + DI)
Multiply both sides by 2
6*2 = 4 + DI
12 = 4 + DI
12 - 4 = 4 + DI - 4
8 = DI
DI = 8 cm